The effect of liquid inorganic fertilizer on the growth of seven sugarcane (Saccharum officinarum L.) clones for sugar factory in Indonesia - Lailiyah, Wiharyanti Nur; Budi, Setyo; Zumroh, Arofatuz; Nisa, Isnaini Maulidatu; Nurjanah, Indah; Husain, Mochammad Jamaluddin (Universitas Lancang Kuning, 2024)
Sugarcane (Saccharum officinarum L.) is a type of plantation crop that has high economic value as the main ingredient for sugar production. Indonesia's sugar demand increases every year, but it is not accompanied by an increase in sugar production. Problems that cause low sugar production include seed quality, fertilizer availability, water availability, slash-and-carry management, and inadequate soil conditions. Increasing sugarcane productivity and production is related to the level of yield production. The availability of new superior varieties (VUB) is one way that can be done to produce high sugar production. The continuous use of excessive inorganic fertilizers can cause problems in agriculture. The purpose of this study was to analyze the effect of inorganic liquid fertilizer on the growth of seven sugarcane clones (Saccharum officinarum L.) in Sidoarjo Regency, Indonesia. This research was conducted in the Sugarcane Research and Development Center (P3T) garden and in collaboration with PG Krembung PT Perkebunan Nusantara X (PTPN X) in October-January 2021. This study used a one-factor Randomized Group Design (RAK) with 9 treatments and 3 replications. Parameters observed in this study were stem diameter, stem length, and number of stems. The results showed that the growth of the K4 sugarcane clone (SB 11 clone) was higher than the K5 (PS 881 clone). Petrovita fertilizer application resulted in more optimal growth in sugarcane clone.